Printed antennas for wireless communications (John Wiley & Sons, Ltd., 2007)
Also known as microstrip antennas, these devices are mounted on the exterior of airplanes and spacecraft as well as used in mobile communication devices. They are compact, durable, accommodating and cheap, and this collection of articles by academics and practitioners offers help on both theory and applications to designers. They cover fundamental wideband printed antennas such as multilayered patch antennas, printed quasi-Yagi antennas, printed spiral antennas, printed folded "beverage" antennas and printed slot antennas, applications in wireless systems, such as planar inverted-F antennas, small patch-based antennas, small multiband printed monopole antennas, and printed antennas in packages, and advanced concepts such as printed reflectarray antennas, antennas on artificial magnetic conductors, transceiver architectures for highly integrated RF front-ends, frequency-agile antennas for a software-define and cognitive radio, and antenna evaluation for communications with diversity and multiple input/multiple output.